123456789101112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081 |
- from sympy.core.numbers import Integer
- from sympy.core.symbol import symbols
- from sympy.physics.quantum.dagger import Dagger
- from sympy.physics.quantum.commutator import Commutator as Comm
- from sympy.physics.quantum.operator import Operator
- a, b, c = symbols('a,b,c')
- n = symbols('n', integer=True)
- A, B, C, D = symbols('A,B,C,D', commutative=False)
- def test_commutator():
- c = Comm(A, B)
- assert c.is_commutative is False
- assert isinstance(c, Comm)
- assert c.subs(A, C) == Comm(C, B)
- def test_commutator_identities():
- assert Comm(a*A, b*B) == a*b*Comm(A, B)
- assert Comm(A, A) == 0
- assert Comm(a, b) == 0
- assert Comm(A, B) == -Comm(B, A)
- assert Comm(A, B).doit() == A*B - B*A
- assert Comm(A, B*C).expand(commutator=True) == Comm(A, B)*C + B*Comm(A, C)
- assert Comm(A*B, C*D).expand(commutator=True) == \
- A*C*Comm(B, D) + A*Comm(B, C)*D + C*Comm(A, D)*B + Comm(A, C)*D*B
- assert Comm(A, B**2).expand(commutator=True) == Comm(A, B)*B + B*Comm(A, B)
- assert Comm(A**2, C**2).expand(commutator=True) == \
- Comm(A*B, C*D).expand(commutator=True).replace(B, A).replace(D, C) == \
- A*C*Comm(A, C) + A*Comm(A, C)*C + C*Comm(A, C)*A + Comm(A, C)*C*A
- assert Comm(A, C**-2).expand(commutator=True) == \
- Comm(A, (1/C)*(1/D)).expand(commutator=True).replace(D, C)
- assert Comm(A + B, C + D).expand(commutator=True) == \
- Comm(A, C) + Comm(A, D) + Comm(B, C) + Comm(B, D)
- assert Comm(A, B + C).expand(commutator=True) == Comm(A, B) + Comm(A, C)
- assert Comm(A**n, B).expand(commutator=True) == Comm(A**n, B)
- e = Comm(A, Comm(B, C)) + Comm(B, Comm(C, A)) + Comm(C, Comm(A, B))
- assert e.doit().expand() == 0
- def test_commutator_dagger():
- comm = Comm(A*B, C)
- assert Dagger(comm).expand(commutator=True) == \
- - Comm(Dagger(B), Dagger(C))*Dagger(A) - \
- Dagger(B)*Comm(Dagger(A), Dagger(C))
- class Foo(Operator):
- def _eval_commutator_Bar(self, bar):
- return Integer(0)
- class Bar(Operator):
- pass
- class Tam(Operator):
- def _eval_commutator_Foo(self, foo):
- return Integer(1)
- def test_eval_commutator():
- F = Foo('F')
- B = Bar('B')
- T = Tam('T')
- assert Comm(F, B).doit() == 0
- assert Comm(B, F).doit() == 0
- assert Comm(F, T).doit() == -1
- assert Comm(T, F).doit() == 1
- assert Comm(B, T).doit() == B*T - T*B
- assert Comm(F**2, B).expand(commutator=True).doit() == 0
- assert Comm(F**2, T).expand(commutator=True).doit() == -2*F
- assert Comm(F, T**2).expand(commutator=True).doit() == -2*T
- assert Comm(T**2, F).expand(commutator=True).doit() == 2*T
- assert Comm(T**2, F**3).expand(commutator=True).doit() == 2*F*T*F + 2*F**2*T + 2*T*F**2
|